The Mechanic Ear: North American Sound Poetry in the Digital Age - Goicoechea, María; Salceda, Víctor (Complutense Journal of English Studies, 2015)
This essay provides a revision of North American sound poetry from the perspective of the digital culture. In an effort to describe the role that sound plays in digital literature creations, we have tried to find points of suture between the practitioners of sound poetry of different decades and the contemporary practices of sound and digital poetry. The main objective is to establish a relation between these poetic genres, as they both emphasize the aural dimension as well as challenge academic categorization and print tradition alike. We will discuss the work of three seminal practitioners of sound poetry: Jerome Rothenberg, John Cage, and Jackson Mac Low. We examine their proposals alongside those of contemporary artists that belong to what we describe as the posthuman phase of sound poetry: Jim Andrews, Christian Bök, and Tracie Morris. Through the comparison of seminal sound poetry practitioners of the 1960s with contemporary North American poets that have recuperated poetry’s performative dimension, we explore the new poetical effects produced by the digitalization of the human voice alone or in combination with other sounds, images and text. From Native American chants to the digital poetry found on the Web, we will explore the influence of the medium as well as other cultural factors influencing the production of oral poetry and its dissemination. Digital poetry nourishes itself from previous literary traditions as well as from the multimedia convergence favoured by the digital medium. Despite being latecomers to the field of sound poetry, North American sound poets have influenced the work of artists at a global level, and continue to do so, both through their digital creations and through their live performances.